2013
DOI: 10.1063/1.4805359
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Na+ and K+ doping on the properties of sol-gel deposited 2-hydroxy-1,4-naphthoquinone thin films

Abstract: We describe the use of 2-hydroxy-1,4-naphthoquinone (HNQ) thin films as a potential water vapor and electrolyte sensing material towards the goal of non-invasive relative humidity and sweat detection. We have successfully made HNQ sol-gel thin films and studied the effects of sodium and potassium ions on their optical and electrical characteristics. Ultraviolet-visible absorbance and Fourier transform infrared spectroscopy measurements along with scanning electron microscopy demonstrated that we were able to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…31 It turns from pale orange to dark orange (see Figure 2(a) inset). The main reason behind the color change is that the hydroxyl group of HNQ (see Figure 1 inset) is deprotonated, and the negatively charged oxygen atom is attached to positively charged sodium or potassium ions, forming a doped HNQ structure.…”
Section: Sweat Chemical Analysis Using Hnq Dyementioning
confidence: 97%
See 2 more Smart Citations
“…31 It turns from pale orange to dark orange (see Figure 2(a) inset). The main reason behind the color change is that the hydroxyl group of HNQ (see Figure 1 inset) is deprotonated, and the negatively charged oxygen atom is attached to positively charged sodium or potassium ions, forming a doped HNQ structure.…”
Section: Sweat Chemical Analysis Using Hnq Dyementioning
confidence: 97%
“…The main reason behind the color change is that the hydroxyl group of HNQ (see Figure 1 inset) is deprotonated, and the negatively charged oxygen atom is attached to positively charged sodium or potassium ions, forming a doped HNQ structure. 31 This effect changes the electron density of the FIG. 1.…”
Section: Sweat Chemical Analysis Using Hnq Dyementioning
confidence: 98%
See 1 more Smart Citation
“…Correct and immediate determination of dehydration level in the body is vital because any change from normal levels may induce health problems. Developing highly sensitive and selective sweat sensors has attracted much attention due to its importance in areas of biotechnology and clinical diagnostics [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, researchers have recently focused on the investigations of un-doped and doped nanostructured metal oxide films. For example, doping with alkali metals such as Sodium and Potassium enhances the conductivity, sensitivity and selectivity of humidity sensors [10][11][12]. It was reported that doping thin films with alkali metals affects luminescence and electrical properties of films [13,14].…”
Section: Introductionmentioning
confidence: 99%